2019
DOI: 10.1002/adfm.201907064
|View full text |Cite
|
Sign up to set email alerts
|

Self‐Hydrophobization in a Dynamic Hydrogel for Creating Nonspecific Repeatable Underwater Adhesion

Abstract: Adhesive hydrogels are widely applied for biological and medical purposes; however, they are generally unable to adhere to tissues under wet/underwater conditions. Herein, described is a class of novel dynamic hydrogels that shows repeatable and long‐term stable underwater adhesion to various substrates including wet biological tissues. The hydrogels have Fe3+‐induced hydrophobic surfaces, which are dynamic and can undergo a self‐hydrophobization process to achieve strong underwater adhesion to a diverse range… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
160
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(175 citation statements)
references
References 38 publications
0
160
0
Order By: Relevance
“…The quantified adhesion ability can be applied to wound dressings and adhesives for tissue healing ( Figure 9 ). At the same time, the hydrogel preparation method is simple and easy to operate during the preparation process, and has long-term stability, which greatly expands the application of hydrogels in underwater or humid environments, especially in the potential of body fluids or blood environments [ 95 ]. Zhang et al [ 96 ] summarized the technical difficulties in the underwater adhesion of hydrogel materials, focused on the relevant parameters that characterize the underwater mechanical properties of hydrogels, and established the experimental design and evaluation methods for hydrogel materials based on this, and summarized the unique properties, synthesis method, and preparation process of the biomimetic viscous hydrogel, and proposed new insights into the underwater adhesion mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…The quantified adhesion ability can be applied to wound dressings and adhesives for tissue healing ( Figure 9 ). At the same time, the hydrogel preparation method is simple and easy to operate during the preparation process, and has long-term stability, which greatly expands the application of hydrogels in underwater or humid environments, especially in the potential of body fluids or blood environments [ 95 ]. Zhang et al [ 96 ] summarized the technical difficulties in the underwater adhesion of hydrogel materials, focused on the relevant parameters that characterize the underwater mechanical properties of hydrogels, and established the experimental design and evaluation methods for hydrogel materials based on this, and summarized the unique properties, synthesis method, and preparation process of the biomimetic viscous hydrogel, and proposed new insights into the underwater adhesion mechanism.…”
Section: Resultsmentioning
confidence: 99%
“…In the case of physical hydrogels, this means the ability to transition from solution (sol) to gelation (gel) state and vice versa. [40] By using the term dynamic in this review, we cover hydrogels that are capable of repetitive recycling, [41] motion, [42] regeneration, [43] self-healing, [44] as well as reversible changes in parameters, [45], for example, size, shape, or charge, without losing their structural integrity. Thus more diverse applications (therapeutic, diagnostic, imaging, etc.)…”
Section: Dynamic Hydrogelsmentioning
confidence: 99%
“…Recent studies have developed adhesives that can remove or absorb interfacial water to form tight contact with tissues. 6,[33][34][35][36][37] Cui et al reported a hyperbranched polymer adhesive containing a hydrophobic backbone and hydrophilic side branches with catechol groups. 6 Upon contacting water, the hydrophobic chains self-aggregate to form coacervates, which displace the interfacial water and promote catechol group exposure, leading to tight contact and strong adhesion between the adhesives and tissues.…”
Section: Introductionmentioning
confidence: 99%
“…Han et al prepared dynamic hydrophobic hydrogels, which repel interfacial water to form tight contact, effective hydrophobic interactions, and strong adhesion on wet substrates. 37 Therefore, removing interfacial water on wet tissues is an effective approach to achieving strong wet adhesion. On the other hand, Yang et al developed a topological adhesion strategy to promote interfacial adhesion by using stitching polymer solutions.…”
Section: Introductionmentioning
confidence: 99%